An Analysis of the Factors Affecting House Prices in Malaysia – An Econometric Approach - Ganeson, Chitra; Abdul Muin, Illias Masri (School of Social Sciences, 2015)
The housing price in Malaysia remains an issue that makes a significant concern to the government as well as potential house buyers at large. The trend has portrayed discernable expansion of housing prices over the years. The study intends to expand on a previous research that only found Gross Domestic Product to have a significant impact on house prices in Malaysia. The results from the study were only able to explain merely 15% of the variations in house pricing. Further research in this study intends to determine other possible factors which could significantly impact the housing price in Malaysia. Variables selected include gross domestic product, inflation, unemployment rate and population. This study covers a period of 23 years from 1988 to 2010 using Multiple Regression method. The aim of the study is to develop a significant econometric model that can be used to forecast Malaysian housing price. By determining the significant factors that could affect housing prices in Malaysia, this study would outline concerns on the factors that contribute to volatile housing prices and hence assist the government in making significant policies in controlling the price of residential properties from escalating uncontrollably which can potentially invite financial disaster such as the subprime crisis that occurred in the USA recently.